Voltage decay and redox asymmetry mitigation by reversible cation migration in lithium-rich layered oxide electrodes - Eum, Donggun; Kim, Byunghoon; Kim, Sung Joo; Park, Hyeokjun; Wu, Jinpeng; Cho, Sung-Pyo; Yoon, Gabin; Lee, Myeong Hwan; Jung, Sung-Kyun; Yang, Wanli; Seong, Won Mo; Ku, Kyojin; et al. (Nature materials, 2020)
Despite the high energy density of lithium-rich layered-oxide electrodes, their real-world implementation in batteries is hindered by the substantial voltage decay on cycling. This voltage decay is widely accepted to mainly originate from progressive structural rearrangements involving irreversible transition-metal migration. As prevention of this spontaneous cation migration has proven difficult, a paradigm shift toward management of its reversibility is needed. Herein, we demonstrate that the reversibility of the cation migration of lithium-rich nickel manganese oxides can be remarkably improved by altering the oxygen stacking sequences in the layered structure and thereby dramatically reducing the voltage decay. The preeminent intra-cycle reversibility of the cation migration is experimentally visualized, and first-principles calculations reveal that an O2-type structure restricts the movements of transition metals within the Li layer, which effectively streamlines the returning migration path of the transition metals. Furthermore, we propose that the enhanced reversibility mitigates the asymmetry of the anionic redox in conventional lithium-rich electrodes, promoting the high-potential anionic reduction, thereby reducing the subsequent voltage hysteresis. Our findings demonstrate that regulating the reversibility of the cation migration is a practical strategy to reduce voltage decay and hysteresis in lithium-rich layered materials. The use of high-energy-density lithium-rich layered-oxide electrodes in batteries is hindered by voltage decay on cycling. Improving the reversible cation migration by altering oxygen stacking is shown to suppress voltage decay and redox asymmetry in lithium-rich nickel manganese oxides.